2005
DOI: 10.1111/j.1365-2109.2005.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 expression in different tissues of Cirrhinus mrigala (Ham.) following heat stress

Abstract: Members of heat shock protein 70 (HSP70) are highly conserved proteins of about 70 kDa and play important roles in protein folding. Levels of these proteins increase when cells are under stress. Environmental temperature influences both the basal and induced levels of HSPs. However, studies on HSPs in fishes from a tropical country such as India are lacking. In the present study, Indian major carp (IMC) Cirrhinus mrigala (Ham.) acclimatized at 25±2°C had high levels of HSP70, viz., 1.2–1.3 ng μg−1 total protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Dietz (1994) observed that the Hsp70 response was absent in brain of Gillichthis mirabilis but present in liver. In contrast, Dias et al (2005) found a strong induction of Hsp70 in liver but not in kidney and gill after heat stress. No information is available on comparison of Hsp level among different tissues in white sturgeon.…”
Section: Resultsmentioning
confidence: 61%
“…Dietz (1994) observed that the Hsp70 response was absent in brain of Gillichthis mirabilis but present in liver. In contrast, Dias et al (2005) found a strong induction of Hsp70 in liver but not in kidney and gill after heat stress. No information is available on comparison of Hsp level among different tissues in white sturgeon.…”
Section: Resultsmentioning
confidence: 61%
“…The expression of Hsp70 in the RBCs of S. aurata under acute thermal stress is consistent with the HSR of RBCs from other fish species (Currie and Tufts, ; Currie et al, ; Lund et al, ; Heredia‐Middleton et al, ). It has been shown that the induction of Hsp70 is more evident compared with other Hsps after thermal stress (Das et al, ). The reduction in the levels of Hsp70 after treatment of RBCs from S. aurata with the inhibitor of p38 MAPK, SB203580, indicates that phosphorylation and hence activation of this kinase controls the expression of Hsp70 in these cells under thermal stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Stress often stimulates Hsp expression in aquatic organisms with Hsp70 induced in hypoxic Nile tilapia Oreochromis niloticus (L.) juveniles (Delaney and Klesius 2004), Indian major carp, Cirrhinus mrigala (Ham. ; Das et al 2005), and the tiger prawn, P. monodon (de la Vega et al 2006). A temperature increase from 21 to 37°C for 30min followed by a 24-h recovery strongly induced Hsp70 in Artemia adults (Clegg et al 2000a), and a non-lethal heat shock from 28 to 37°C for 30min with a 6-h recovery triggered Hsp70 production in gnotobiotic-grown larvae (Sung et al 2007).…”
Section: Discussionmentioning
confidence: 99%